Cell wall polysaccharides determine cooking quality in cassava roots - Sathitnaitham, Sukhita; Ceballos, Hernan; Wonnapinij, Passorn; Kraichak, Ekaphan; Utthiya, Supanut; Suttangkakul, Anongpat; Gomez, Leonardo D.; Kittipadakul, Piya; Siriwong, Nongnuch; Kongsil, Pasajee; Vuttipongchaikij, Supachai (Wiley, 2024)
Social Impact Statement Cassava is a vital food source for millions worldwide, crucial for food security and economic stability. This study analyzed cell wall polysaccharides in cassava roots to understand their impact on cooking properties. We found these polysaccharides influence the textural attributes of cassava roots, essential for both cooking and consumption. The research highlights the need to further identify and analyze cassava cell wall components. By improving our understanding of these components, we can improve food security, affordability, and resilience in diverse regions, ultimately contributing to global food security and better aligning with consumer preferences. Summary The textural attributes of cassava roots significantly influence preferences in cooking and consumption as a food source, yet the specific components dictating these properties remain unclear. We aimed to identify the factors shaping the cooking properties of cassava roots. We conducted a compositional analysis of 22 traits in a diverse F1 biparental population derived from soft‐ and hard‐boiling progenitors. The traits encompassed cooking qualities, starch properties, and cell wall composition. Specific cell wall components including cellulose, xylan, un‐esterified, and methyl‐esterified homogalacturonan (HG) demonstrated a correlation with cooking quality attributes: sensory assessments related to texture (SAT) and water absorption during boiling (WAB). Correlation and regression analyses revealed that these wall components collectively contribute to 20% of SAT variability and 14% of WAB variability. SAT appeared to be influenced by methyl‐esterified and un‐esterified HGs, xylan, and cellulose, impacting the tensile strength of the cell wall. Conversely, WAB appeared to be associated with methyl‐esterified HG, potentially altering water absorption properties. Although genome‐wide association studies (GWAS) were unable to identify significant SNPs for SAT and WAB, notable associations emerged for cellulose, xylan, and un‐esterified‐ and methyl‐esterified HG. Candidate genes associated with these SNPs point towards diverse cell wall‐related proteins, transcription factors, sugar metabolism‐related genes, and glycosyl hydrolases. This study provides insights into the relationship between cassava root compositions and cooking characteristics and the role of wall components in determining the cooking quality of edible cassava. This information represents a substantial contribution towards the development of protocols for selecting varieties with texture preferences.